2020
DOI: 10.3390/molecules25163631
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study on Pseudomonas Aeruginosa Biofilm in the Presence of the Aptamer-DNA Scaffolded Silver Nanoclusters

Abstract: We report the effectiveness of silver nanocluster (Ag-NC) against the biofilm of Pseudomonas aeruginosa (PA). Two DNA aptamers specific for PA and part of their sequences were chosen as templates for growing the Ag-NC. While circular dichroism (CD) studies determined the presence of secondary structures, UV/Vis absorption, and fluorescence spectroscopic studies confirmed the formation of the fluorescent Ag-NC on the DNA templates. Furthermore, mesoscopic physics-based partial wave spectroscopy (PWS) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Then, the degree of structural disorder strength, , is calculated from the rms value of the extracted intensities and the wave vector autocorrelation decay of the reflection intensity ratio, . At the spatial pixel position , the degree of structural disorder strength, is given as 1 , 3 , 22 , 24 , 25 where is the normalization constant, is the average refractive index of the cells/tissue, and is the wavenumber ( ). This disorder strength can be further simplified and expressed as the product of the variance and the spatial correlation length of the refractive index fluctuations, .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the degree of structural disorder strength, , is calculated from the rms value of the extracted intensities and the wave vector autocorrelation decay of the reflection intensity ratio, . At the spatial pixel position , the degree of structural disorder strength, is given as 1 , 3 , 22 , 24 , 25 where is the normalization constant, is the average refractive index of the cells/tissue, and is the wavenumber ( ). This disorder strength can be further simplified and expressed as the product of the variance and the spatial correlation length of the refractive index fluctuations, .…”
Section: Methodsmentioning
confidence: 99%
“…Then, the degree of structural disorder strength, L d-PWS , is calculated from the rms value of the extracted intensities hRðkÞi rms and the wave vector autocorrelation decay of the reflection intensity ratio, CðΔkÞ. At the spatial pixel position ðx; yÞ, the degree of structural disorder strength, L d is given as 1,3,22,24,25 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 1 ; 1 1 6 ; 5 8 5…”
Section: Calculation Of Disorder Strength In the Pws (L D-pws )mentioning
confidence: 99%
“…This aptamer can reduce the mRNA expression level of bacterial biofilm formation genes (e.g., curli gene, interaction, and motility), hinder EPEC K1.1's motility, and prevent bacterial biofilm formation (Oroh et al, 2020). Sengupta et al (2020) reported the effectiveness of aptamer-DNA template silver nanocluster (Ag-NC) for inhibiting P. aeruginosa biofilm formation, and Ag-NC as a sensor is expected to be a new way to detect planktonic cells and biofilm formation. Ning et al (2022) found that simultaneous delivery of penicillin-binding protein 2aspecific DNA aptamer and berberine via graphene oxide effectively inhibited the formation of MRSA biofilms, and this complex could potentially be an effective strategy for the treatment of chronic infections caused by MRSA biofilms.…”
Section: Aptamersmentioning
confidence: 99%
“…Therefore, aptamers have become a major research focus in life sciences and analytical chemistry (Jamei et al, 2021). The analytical methods used for aptamer sensors mainly include surface plasma resonance (Chang, 2021), quartz crystals microbalance (Goda and Miyahara, 2020), colorimetric methods (Tao et al, 2020), spectroscopic techniques (Sengupta et al, 2020) and electrochemical methods (Yang et al, 2019). Among them, electroanalytical sensor based on aptamer is widely used because of its high selectivity and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%